CD8(+) T cells are crucial for the ability of congenic normal mice to reject highly immunogenic sarcomas induced in nude mice with 3-methylcholanthrene - Boesen, M (Blackwell Science Inc, 2000)
An attempt was made to identify the selection pressures put upon a growing tumour by CD8(+) T cells. To this end tumours induced with 3-methylcholanthrene in T cell-deficient nude mice and in congenic T cell-competent nu/+ mice were transplanted to nu/+ recipients. The rejection rate of the sarcomas from nude mice was almost twice that of the sarcomas from nu/+ mice. Depletion of CD8(+) T cells from nu/+ recipients prior to transplantation made them accept nude tumours that were consistently rejected by untreated nu/+ recipients. These findings suggest that a methylcholanthrene sarcoma during its growth in a T cell-competent host adapts to the T cell system through a selective elimination of highly immunogenic tumour cells that are susceptible to CD8(+) T cell-mediated lysis.